Synthesis and solvodynamic diameter measurements of closely related mannodendrimers for the study of multivalent carbohydrate–protein interactions - Chabre, Yoann M.; Papadopoulos, Alex; Arnold, Alexandre A.; Roy, René (Beilstein Journal of Organic Chemistry, 2014)
This paper describes the synthesis of three closely related families of mannopyranoside-containing dendrimers for the purpose of studying subtle structural parameters involved in the measurements of multivalent carbohydrate–protein binding interactions. Toward this goal, two trimers 5 and 9, three 9-mers 12, 17, 21, and one 27-mer 23, varying by the number of atoms separating the anomeric and the core carbons, were synthesized using azide–alkyne cycloaddition (CuAAc). Compound 23 was prepared by an efficient convergent strategy. The sugar precursors consisted of either a 2-azidoethyl (3) or a prop-2-ynyl α-D-mannopyranoside (7) derivative. The solvodynamic diameters of 9-mer 12, 17, and 21 were determined by pulsed-field-gradient-stimulated echo (PFG-STE) NMR experiments and were found to be 3.0, 2.5, and 3.4 nm, respectively.
Keywords: carbohydrates; click chemistry; dendrimers; glycodendrimers; lectins; multivalent glycosystems